Tourism and opportunities for economic development in Asia - Ordóñez de Pablos, Patricia 1975-; Zeyar Myo Aung U 1973- (Advances in hospitality, tourism, and the services industry (AHTSI) book series, 2017)
"This book provides new theories, research findings, and case studies, to enhance understanding and collaboration in issues of tourism and key tourism priorities now and in the future. The book focuses on tourism in Asia, with a special attention to South East Asian nations"...